2014
DOI: 10.4304/tpls.4.4.811-817
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Strategy Instruction on Writing Apprehension and Writing Achievement of EFL Learners

Abstract: Abstract-Writing as a communicative activity imposes great difficulties on EFL learners and both cognitive and affective aspects of writing have a sharing part in this complex process. The current study aimed to explore the effect of explicit writing strategy instruction, prewriting strategies in particular on reducing writing apprehension, and promoting writing performance.42 intermediate EFL students participated in this study, 28 students in two experimental groups received the treatment and the results com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Configurations C3–C6 are categorized as a social-behavior-driven type due to their shared core conditions centered on the incorporation of social-behavioral strategies. This finding aligns with the work Mohseniasl 69 , who highlights the role of explicit writing strategy instruction in alleviating writing difficulties, supporting our observation that focusing on specific types of writing strategies, such as social-behavioral and motivational, can lead to improved writing outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Configurations C3–C6 are categorized as a social-behavior-driven type due to their shared core conditions centered on the incorporation of social-behavioral strategies. This finding aligns with the work Mohseniasl 69 , who highlights the role of explicit writing strategy instruction in alleviating writing difficulties, supporting our observation that focusing on specific types of writing strategies, such as social-behavioral and motivational, can lead to improved writing outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Machida and Dalsky (2014) showed that concept mapping technique helps learners with low writing anxiety more than their counterparts with high writing anxiety in the quality of their writing. Moreover, Mohseniasl (2014) indicated that explicit instruction of writing strategy has a positive effect on the writing performance of learners who experience high level of writing apprehension. In addition, Parilasanti, Suarnajaya, and Marjohan (2014) claimed that RAFT strategy has more positive effect on high anxious learners' writing competency than conventional strategy.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…Therefore, the more proficient the participants, the more information they receive to produce better writing (Raoofi et al, 2017). To support this, according to Mohseniasl (2014), the execution of a clearly defined strategy for the teacher's teaching may make a massive difference in the learning process for students. Teachers' explicit instruction influenced the presence of actively used strategy in writing in teaching writing, making students more aware of employing strategy in writing and helping the students lessen their writing anxiety (Masriani et al, 2018).…”
Section: Writing Anxietymentioning
confidence: 99%